Analysis and Feasibilty of Nano-Lubricant in Vapour Compression Refrigeration System. (2018) - Santhana Krishnan, R.; Arulprakasajothi, M.; Logesh, K.; Dilip Raja, N.; Rajendra, Mycherla
Abstract: This paper deals with the analysis and feasibility of nano-lubricants in vapour compression refrigeration system. Refrigeration system has become one of the major energy consumer and hence in the present scenario of depleting resources, it is the need of the hour to enhance the energy efficiency of the refrigeration systems. This project incorporates nano-particles in lubricants which helps in increasing the heat transfer characteristics of the refrigeration system hence decreasing the work done by the compressor. The refrigerant used is R134a as it has zero ozone depletion potential and is environment-friendly. The lubricant used was Poly-ol Ester (POE). The various nanoparticles used are Al2 O3, SiO2, ZrO2 and CNT. The nano-particles were suspended into the lubricant by means of ultrasonification and magnetic stirring to disperse the nanoparticles uniformly in the system.